2021
DOI: 10.1007/s00345-021-03768-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nomogram predicting the probability of stone free rate in patients with ureteral stones eligible for semi-rigid primary laser uretero-litothripsy

Abstract: Purpose Few tools are available to predict uretero-lithotripsy outcomes in patients with ureteral stones. Aim of our study was to develop a nomogram predicting the probability of stone free rate in patients undergoing semi-rigid uretero-lithotripsy (ULT) for ureteral stones. Methods From January 2014 onwards, patients undergoing semi-rigid Ho: YAG laser uretero-lithotripsy for ureteral stones were prospectively enrolled in two centers. Patients were preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Studies have demonstrated that the surgical methods can greatly affect the outcomes, four times of stone-left incidence of flexible ureteroscopy less than ureteroscopy in this paper. In addition, there were also lots of researches that includes all ureteral stones, which in our opinion was meaningless (16). Unless those rare stones, nearly all distal and middle ureteral stones can reach a high SFR under standard skilled procedures.…”
Section: Discussionmentioning
confidence: 93%
“…Studies have demonstrated that the surgical methods can greatly affect the outcomes, four times of stone-left incidence of flexible ureteroscopy less than ureteroscopy in this paper. In addition, there were also lots of researches that includes all ureteral stones, which in our opinion was meaningless (16). Unless those rare stones, nearly all distal and middle ureteral stones can reach a high SFR under standard skilled procedures.…”
Section: Discussionmentioning
confidence: 93%
“…Operation time referred to a period from the time when the scope was inserted into the body to the time when the scope was removed from the body. For the definitions on stone-free status, different studies [ 10 , 11 ] has some differences on the size of stone fragments. In this study, stone-free status referred to the scope smoothly reaching target calices and pulverizing calculi into small fragments less than 2 mm [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Stone length and location, number of stones, and the presence of pyuria were significant independent factors correlated with SFR. Meanwhile, single stone, stone size, distal position, and absence of hydronephrosis, which are significant predictive factors of stone-free status, were used in another nomogram for predicting the outcome of rigid URS for ureteral stones (13) (15). This study revealed that stone volume, presence of lower pole stone, operator with an experience of >50 flexible URS, stone number, and presence of hydronephrosis were stone-free status.…”
mentioning
confidence: 88%